Investigation of oral and oropharyngeal squamous cell carcinoma in young adults - O'Regan, Esther (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Histopathology & Morbid Anatomy, 2006)
While oral and pharyngeal squamous cell carcinoma is classically a disease of older male smokers, this tumour type can occur in young patients with minimal or no exposure to the traditional risk factors. The prognosis remains poor for all of these patients irrespective of age or smoking status, despite improvements in treatment modalities. The purpose of this project was to use new molecular techniques to enhance the understanding we have of oral and oropharyngeal SCC, paying particular attention to the cancer occurring in young patients (under 40 years old). The project began by comparing features of oral and pharyngeal SCC in a group of Irish patients with results published from other countries. Concurring with previous reports, this study found a highly significant association between both the age and smoking status of the HNSCC patient and site of tumour occurrence, thus setting the scene for the subsequent molecular analysis performed on tumour samples from a selection of these patients. To begin the molecular analysis of these young patients, a comprehensive microarray comparative genomic hybridisation analysis was performed. Our experiments on DNA from patients with oral and oropharyngeal SCC have shown that far less genomic aberrations occurred in the young non-smoker samples compared with the old smokers. A gene of interest that is very often deleted in head and neck cancer is p16.
Keywords: Histopathology, Ph.D.; Ph.D. Trinity College Dublin